Citrus aurantifolia essential oil: antiaging potential through integrated in vitro and in silico studies - Yasmin A. Elkhawas; Mahmoud A. El Hassab; Omkulthom Al kamaly; Ahmed T. Negmeldin; Ahmed T. Negmeldin; Taghreed A. Majrashi; Wagdy M. Eldehna; Nada M. Mostafa (Frontiers in Chemistry, 2025)
IntroductionNatural skincare products and cosmetic preparations have gained popularity among consumers in recent years, prompting cosmetic companies to develop more natural offerings. These products often incorporate plant extracts known for their anti-aging, anti-wrinkle, and depigmentation properties.MethodsUsing gas chromatography-mass spectrometry, this study examined the volatile compounds in both fresh and dry Citrus aurantifolia (key lime) fruit essential oils. The oils’ anti-aging and antioxidant activities were assessed through in vitro anti-collagenase and anti-elastase assays.ResultsIn vitro analysis revealed good inhibition of elastase and collagenase enzymes by fresh key lime essential oil, with IC50 values of 145.02 and 63.97 μg/mL, respectively, compared to positive controls (daidzein for collagenase, piroxicam for elastase), in comparison to dry key lime oil (IC50 = 223.14 and 109.57 μg/mL, respectively). The antioxidant activity of the oils was evaluated using the ABTS (2,2’-azino-bis(3-ethylbenzothiazoline6-sulfonic acid)) radical scavenging assay. The fresh key lime oil demonstrated stronger antioxidant activity (37.76 ± 0.80 μM Trolox equivalent (TE)/g) compared to the dry key lime oil (27.76 ± 1.11 μM TE/g), suggesting that it retains more bioactive compounds essential for radical scavenging activity. Additionally, molecular docking was performed to analyze interactions between the main metabolites and the targeted enzymes active sites. Molecular docking analysis showed excellent binding scores for the three main metabolites.ConclusionThe anti-aging potential of fresh key lime essential oil may be attributed to its major compounds. These findings suggest that key lime essential oil could be a promising natural ingredient for anti-aging skincare formulations.